Efficiency and Competition in the Malaysian Banking Market: Foreign versus Domestic Banks - Rossazana Ab-Rahim (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2017)
The aim of this paper is to investigate efficiency performance of Malaysian banking market using data envelopment analysis approach in the context of the increasing presence of foreign banks. Specifically, two measures of efficiency are constructed, cost and profit efficiency by utilizing bank-level data of Malaysian commercial banks, over the period 2003 to 2014. The results obtained show the domestic banks are more efficient than the foreign banks counterparts for both measures of efficiency. Next, the Lerner Index approach is employed to measure competition and finally, Granger causality tests are undertaken to answer the question, does competition foster efficiency? The results of causality tests support a positive effect of competition on cost and profit efficiency of Malaysian banks. With regard to the financial liberalization, the findings imply that higher competitive pressure may be offset the market power of individual banks; however, eventually it will results in efficiency gains of Malaysian banks.